Mutual Exclusion Method in Client-Side Aggregation of Cloud Storage - Seo, Dongmahn; Kim, Suhyun; Song, Gyuwon (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2017)
Consumers continue to produce and spend a huge amount of data using consumer electronic devices. To store consumers' data, a huge volume of storage is needed. A cloud-of-clouds which is a virtual cloud storage service using heterogeneous public cloud storage services can be a solution. To support concurrent accesses for multiple consumers and devices, a mutual exclusion in a cloud-of-clouds is necessary. In this paper, we propose a mutual exclusion method for concurrent accesses in a cloud-of-clouds. The proposed method includes an atomic operation for cloud-of-clouds, a deadlock recovery and a race condition control.